Late-Onset Capsular Block Syndrome: A One Year Follow-up Case Report: Doi: 10.36351/pjo.v40i2.1676 - Ludovico Iannetti1; David Shaholli; Mauro Salducci (Pakistan Journal of Ophthalmology, 2024)
We report a case of late Capsular Block Syndrome (CBS) in a patient who underwent cataract surgery 12 years back. It was diagnosed with slit-lamp examination and by using anterior segment optical coherence tomography (AS-OCT) that showed hyper-reflective material trapped in the capsular bag, between the IOL posterior surface and the posterior capsule. Anterior capsule fibrosis was seen in both eyes but in the left eye capsulorhexis showed irregular margins and had a smaller diameter compared to the right eye. The CBS was treated with Nd:YAG laser capsulotomy allowing rapid evacuation of liquid towards the vitreous chamber. Complete resolution of CBS was confirmed by AS-OCT. Best Corrected Visual Acuity (BCVA) of left eye improved from 0.2 logMAR before treatment to 0.0 logMAR one week after treatment. BCVA remained unchanged after one year of follow-up with no sign of new posterior capsular fibrosis.